Historisch-vergleichende methode in der europaischen sprachwissenschaft der ersten halfte des 19. ahrhunderts: grimmsches gesetz - Kantur, К. А.; Контур, К. О.; Контур, К. А. (Одеса : Гельветика, 2014)
This article is an attempt to characterize the operational component of comparative historical method in European linguistics of the first quarter of the XIX century. The material of the first Germanic consonants transmission (Grimm's Rule). The author shows that a systematic approach to language was the first admission of the genetic identification offacts which prevailed over the linguistic reconstruction procedure in comparative date. The features of the first study of Germanic consonants in the Comparative study of theXIX—XX centuries have been learnt with the emphasis on the methodological aspects.
Kantur К.А. Historisch-vergleichende methode in der europaischen sprachwissenschaft der ersten halfte des 19. ahrhunderts: grimmsches gesetz / К. А. Kantur // Одеський лінгвістичний вісник. – 2015. – Вип. 5. – Т. 1 – С. 197-201.
Keywords: comparative-historical method; operational component; genetic; порівняльно-історичний метод; операційний компонент; генетичне ототожнення фактів; лінгвістична реконструкція; закон Грімма; лінгвоісторіографічний аспект; сравнительно-исторический метод; операционный компонент; генетическое отождествление фактов; лингвистическая реконструкция; закон Гримма; лингвоисториографичный аспект